PROHIBITION OF ETHIC MARRIAGE IN MINANGKABAU CULTURE AND ITS IMPLICATIONS ON CULTURAL COUNSELING - Yuliana Nelisma (Advice: Jurnal Bimbingan dan Konseling, 2022)
In Minangkabau culture, marriage of one tribe is a prohibited marriage. The perpetrators will be given a fairly heavy customary sanction, namely being ostracized from their extended family, community and expelled as long as they are customary. The lineage of both husband, wife and children may not use tribal names. Likewise with other customary rights. This type of research is descriptive analytical. Data collection techniques in this study using library techniques. Sources of data in this study are books, scientific journals, documents, magazines, laws and regulations and relevant research results which are accessed through libraries and through open journal search systems via the internet.